Integrating Environmental Sustainability into HR Practices: A Study on the Impact of Green HRM on Employee Engagement and Retention - Razvi, Syed Shakir; Khan G, Mohamed Abbas; Yahiya Z, Mohammed; Basha, Ameen (International Journal of Sustainable Business, Management and Accounting, 2026)
Background of study: Growing environmental challenges and increasing stakeholder pressure have compelled organizations to integrate sustainability into their core business strategies. Human Resource Management plays a critical role in this transformation through the adoption of Green Human Resource Management (GHRM) practices, which embed environmental principles into recruitment, training, performance management, and workplace design. However, empirical evidence on how GHRM influences employee engagement and retention remains limited, particularly across diverse organizational contexts. Aims and scope of paper: This paper aims to examine the impact of Green HRM practices—specifically green training programs, eco-friendly workplace design, and green recruitment policies—on employee engagement and retention intention. The scope of the study focuses on employees working in organizations that have implemented sustainability-oriented HR practices across various industries. Methods: A quantitative, cross-sectional research design was employed. Data were collected through structured questionnaires distributed to 200 employees using purposive sampling. Descriptive statistics, correlation analysis, and analysis of variance (ANOVA) were applied to examine relationships and differences among variables. Reliability and validity tests confirmed the robustness of the measurement instruments. Result: The findings indicate strong positive relationships between Green HRM practices and employee engagement, as well as between engagement and retention intention. All GHRM variables recorded high mean scores, and ANOVA results revealed significant differences in engagement and retention based on the level of GHRM implementation. Conclusion: The study concludes that Green HRM practices significantly enhance employee engagement and retention. Integrating environmental sustainability into HR policies not only supports organizational sustainability goals but also strengthens employee commitment and long-term organizational performance.